Strategi Penataan Permukiman Nelayan Keberlanjutan di Tepi Sungai Kaliyasa - Ardhi, Prabhaskara Henry; Sri Rejeki, V.G.; Ardiyanto, Antonius (RUAS, 2022)
The Kaliyasa River is a vital means for fishermen, especially traditional fishermen who live around the river. Since the construction of the Cilacap Fishing Port, many migrants started to settle and overtime the population crowded the area uncontrollably and marginalized. This study focused on the strategy of reorganizing fishermen’s settlements with a sustainable development and waterfront development approach as well as the regulation of PERMEN no. 28 of 2015, Descriptive-qualitative method has being used to explain the conditions in the study area, The data collection using desk study and field study methods, from the findings confirmed by the theory of waterfront and sustainable development in order to obtain the right reorganizing strategy. The result of this research is a settlement reorganizing strategy that applies the principle of waterfront development. This principle is applied through social aspects by creating open public spaces, piers placement, and public counseling about river border regulations. Environmental aspects with the arrangement of trash bins on the banks of the river as well as the establishment of waste management institution, management of green open spaces, and solution for illegal buildings in river bank areas. Economic aspects by improving dock infrastructure to support fishing activities, as well as reorganizing marine product trade zone. The preservation aspect aims to preserve the identity of the Kaliyasa river as water transportation route and fishermen's settlements.